2011
DOI: 10.1590/s1519-38292011000100009
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive breast feeding and prevention of diarrheal diseases: a study in Qatar

Abstract: OBJECTIVE: to explore the relationships between breast feeding and diarrhea and to assess the effect of exclusive breast feeding (EBF) on reducing the risk of diarrhea in Qatar. METHODS: this is a cross sectional survey carried out at the Well baby clinics and Pediatric clinics in the 11 Primary Health Care Centers and Hamad General Hospital, Hamad Medical Corporation, in Qatar. A multistage sampling design was used and a representative sample of 1500 Qatari infants and preschool children with an age range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1
7

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 9 publications
3
19
1
7
Order By: Relevance
“…But frequent (two or more) attack of diarrhea occurred in non-exclusive breast fed children; in breast fed plus formula fed children 35 (59.3%), exclusively formula fed 10 (71.4%) and exclusively breast fed 21 (27.3%). Abdulbari Bener et al 7 study on exclusive breast feeding and prevention of diarrheal diseases showed more than half of the infants (59.3%) were exclusively World Health Organization (WHO) recommends exclusive breast feeding for first six months of life and continuation of breast feeding for two years or beyond 9,10 . We found 59 patients developed first attack of diarrhea by 6 months of age, of whom most children were from non-exclusively breast fed group; there were breast fed plus formula fed children 41 (69.5%), exclusively formula fed 12 (20.3%) and exclusively breast fed only 6 (10.2%).…”
Section: Resultsmentioning
confidence: 99%
“…But frequent (two or more) attack of diarrhea occurred in non-exclusive breast fed children; in breast fed plus formula fed children 35 (59.3%), exclusively formula fed 10 (71.4%) and exclusively breast fed 21 (27.3%). Abdulbari Bener et al 7 study on exclusive breast feeding and prevention of diarrheal diseases showed more than half of the infants (59.3%) were exclusively World Health Organization (WHO) recommends exclusive breast feeding for first six months of life and continuation of breast feeding for two years or beyond 9,10 . We found 59 patients developed first attack of diarrhea by 6 months of age, of whom most children were from non-exclusively breast fed group; there were breast fed plus formula fed children 41 (69.5%), exclusively formula fed 12 (20.3%) and exclusively breast fed only 6 (10.2%).…”
Section: Resultsmentioning
confidence: 99%
“…Estudo transversal desenvolvido no Catar com 1.278 crianças identificou que o risco de apresentar a diarreia foi mais alto naquelas que faziam uso de fórmulas lácteas (48,7%) e nas que foram parcialmente amamentadas (37.3%) em comparação com àquelas que recebiam aleitamento materno exclusivo (32.5%) (14) . Pesquisa realizada em Fortaleza detectou uma prevalência de 12,4% casos de diarreia infantil, dos quais 60% e 26,7%…”
Section: Discussionunclassified
“…13 Banyak penelitian terdahulu yang sudah membuktikan bahwa pemberian ASI eksklusif dapat menurunkan risiko diare pada bayi dan anak, seperti hasil penelitian yang dilakukan Kramer dkk., 6 Diallo dkk., 7 Biswas dan Mandal, 8 serta Bener dkk. 19 Lama pemberian ASI tanpa melihat eksklusivitas pemberiannya, berbanding terbalik dengan diare pada bayi. 20 Penelitian ini mendukung pernyataan di atas dengan ditemukan hubungan yang bermakna pemberian ASI eksklusif dan lama pemberian ASI dengan prevalensi diare.…”
Section: Pembahasanunclassified